OS 26-04 TARGETING CARE GAPS IN PATIENTS WITH HYPERTENSION: A QUALITY IMPROVEMENT PROJECT UTILIZING EMR HYPERTENSION DASHBOARDS AND A CHRONIC DISEASE COORDINATOR. (September 2016) - Ngui, Daniel; Qiu, Michael J.H.; Mann, Michael
Abstract : Objective: In order to address the systematic and practice management issues associated with managing hypertension, we undertook a quality improvement project at a multi-physician clinic in Vancouver, British Columbia, Canada. We piloted an evidence-based electronic medical record (EMR) hypertension management dashboard based on the 2014 Canadian Hypertension Education Program (CHEP) guideline recommendations. Since June 1, 2015, our chronic disease coordinator utilized our EMR HTN Dashboard to generate patient recalls, create physician reminders and to enhance internal clinic referrals to provide 1:1 patient hypertension self-management education by physicians and our clinical pharmacist team. We wanted to assess the potential benefits for patient centered care and test the financial sustainability of this pilot project. Design and Method: We retrospectively compared our EMR data for a 6-month pre-implementation period (Jan 1 to June 30, 2015) and post-implementation (July 1 to Dec 31, 2015) to understand the value of our pilot EMR Dashboard and CDM coordinator role. Results: Our analysis revealed more patients were seen for chronic disease reviews jointly by the pharmacist and physician as opposed to physician only hypertension visits post EMR dashboard and CDM coordinator implementation. Physician capacity was improved, we were able to achieve more guideline based recommendations through improved patient education and our CDM program remained cash flow positive (table 1). Conclusions: By piloting a population health based approach where an EMR hypertension dashboard was used by a chronic disease coordinator to identify care gaps in hypertension for our office, we have attempted to move towards proactive care, supporting the concept of a patient centered medical home. Further study is required, but this proof of concept quality improvement program has allowed us to potentially find a self-sustaining method of incorporating medical informatics, allied health team members and the chronic disease model of care within our clinic. Figure. No caption available.